2022
DOI: 10.1002/pbc.29917
|View full text |Cite
|
Sign up to set email alerts
|

Meditation reduces brain activity in the default mode network in children with active cancer and survivors

Abstract: Background: Mounting evidence demonstrates that meditation can lower pain and emotional distress in adults, and more recently, in children. Children may benefit from meditation given its accessibility across a variety of settings (e.g., surgical preparation).Recent neuroimaging studies in adults suggest that meditation techniques are neurobiologically distinct from other forms of emotion regulation, such as distraction, that rely on prefrontal control mechanisms, which are underdeveloped in youth. Rather, medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…These relationships were not explained fully by age ( Tables S3 and S4 ). As there was a relatively small range of ages (1215) and a wider range of pubertal development, pubertal development was included as a covariate in further analyses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These relationships were not explained fully by age ( Tables S3 and S4 ). As there was a relatively small range of ages (1215) and a wider range of pubertal development, pubertal development was included as a covariate in further analyses.…”
Section: Resultsmentioning
confidence: 99%
“…As there was a relatively small range of ages (12)(13)(14)(15) and a wider range of pubertal development, pubertal development was included as a covariate in further analyses.…”
Section: Self-report and Demographicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using neuroimaging, we found that greater trait mindfulness was associated with lower anxiety and increased markers of neural flexibility in children (Marusak et al, 2018). We also found that active meditation, such as focused attention to the breath, was associated with lower activity in the brain's default mode network, which is implicated in distress and rumination, in children with cancer (Hehr et al, 2022).…”
Section: Mind–body Interventions: the “What” “How” And “Why”mentioning
confidence: 94%